Utricularia geminiscapa Benj. (Lentibulariaceae): A new angiospermic record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not availableBangladesh J. Plant Taxon. 27(1): 191-194, 2020 (June)